Flexing and digital social pleasure: a socioeconomic study of fake lifestyles on Instagram - Mubayyin, Afief (PT. Anagata Sembagi Education, 2025)
This study explores the phenomenon of flexing as a status representation strategy in the digital visual economy, particularly on the Instagram platform. Flexing, or the practice of visually showcasing a luxurious lifestyle, is understood not simply as personal expression, but as part of the logic of affective and algorithmic capitalism that shapes the digital habitus of contemporary society. In this context, self-image becomes a symbolic commodity exchanged for visibility and social validation, creating performative pressures that are both emotional and structural. This study uses a descriptive qualitative approach through netnographic observation and semi-structured interviews to uncover how millennials and Gen Z individuals engineer their lifestyle images as a form of aesthetic and affective labor. The analysis shows that flexing blurs the boundaries between reality and illusion, reproducing inequality through commodified visual aesthetics. Within this dynamic, flexing can be read as a form of co-optation of neoliberal ideology, but also as a symbolic strategy for negotiating social position within an exclusionary structure. This research emphasizes that digital social pleasure is not a neutral space, but rather an arena filled with power relations, algorithmic pressures, and fantasies of meritocracy. Thus, fake lifestyles on social media are a structural symptom of the crisis of representation and the pressures of performativity in the contemporary digital economy.